Disharmoni dalam Dinamika Penyelenggaraan Pemerintahan Daerah - Junus, Dikson; Potabuga, Sucipto (Gorontalo Journal of Government and Political Studies, 2018)
The dynamics of good governance at the central government level to the level of local government is inseparable from the conflict. Conflict usually occurs horizontally or vertically, causing disharmony in the administration. In the period 2014-2015 in the Province of Gorontalo had experienced dynamics in governance that led to poor inter-regional relations. This paper will discuss the disharmony of Governor and Mayor relationship with the focus of discussion on the function of coordination and supervision in the implementation of local government. The results show that the disinclination of government relations between provinces and municipalities due to unclear division of authority between governments so that structural and functional coordination is not effective and achievement of goals does not always work as expected. This research suggests changing the mindset of government apparatus in the management and administration of government and strengthening cooperation among local government, so that the dynamics of governance can run effectively and efficiently.